Solow Prices and the Dual Stability Paradox in the Leontief Dynamic System - Zaghini, Enrico (Econometrica, 1971)
[This paper is an attempt at overcoming various logical inconsistencies which have been found in the Leontief dynamic model. It is based on an interpretation of the Leontief model in the framework of a general model of capital accumulation of the Walras-Hicks type. A particular case of such a model, corresponding to the hypothesis of static expectations, turns out to be the competitive capital theory underlying the Leontief model. This theory, capable of defining a meaningful equilibrium even when the Leontief equilibrium based onfull employment of all stocks is not possible, allows us to overcome the difficulty in retaining the economic interpretation of solutions. In the terminology of Hicks (Capital and Growth), this theory solves the problem of the traverse between two full employment equilibria. It will be evident, contrary to current opinion, that output levels and prices are indissolubly connected also inside the Leontief model. Finally, Solow's prices, which give rise to the striking "dual stability paradox," will be discussed. The ultimate reason for such a paradox will be identified as an intrinsic inconsistency in the assumption of correct expectations on which these prices are based.]